2022
DOI: 10.5888/pcd19.210283
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Community-Based Exercise Program for Older Adults in a Mixed Rural/Urban Catchment Area: Silver Sneakers in Central Pennsylvania

Abstract: The purpose of our study was to understand the capacity of Silver Sneakers, a federally funded and community-based exercise program, to serve older adults (aged ≥65 years) in our mixed rural/urban catchment area of central Pennsylvania. We identified 139 registered Silver Sneakers program locations; of these, 18 were closed because of the COVID-19 pandemic. We used questionnaires to interview Silver Sneakers program staff by telephone (n = 80 of 121, response rate of 66%). Most programs were offered by private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Physical activity interventions conducted in a group setting and other active interventions with social components have the potential to target both loneliness and physical activity. Some physical activity programs, such as SilverSneakers, are covered by health plans and can be accessed by Medicare Advantage beneficiaries ( 55 ) and others are offered for nominal fees via older adult centers available to local older adults in a group setting. Additionally, the use of virtual physical activity programs has proliferated since the onset of the pandemic and has the potential to connect older adults who are less mobile or live in remote settings ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity interventions conducted in a group setting and other active interventions with social components have the potential to target both loneliness and physical activity. Some physical activity programs, such as SilverSneakers, are covered by health plans and can be accessed by Medicare Advantage beneficiaries ( 55 ) and others are offered for nominal fees via older adult centers available to local older adults in a group setting. Additionally, the use of virtual physical activity programs has proliferated since the onset of the pandemic and has the potential to connect older adults who are less mobile or live in remote settings ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, older adult physical activity was emphasized again in 2018 with the updated Guidelines (U.S. Department of Health and Human Services, 2018). Along with these federal initiatives, the proliferation of evidence-based exercise and physical activity programs for older adults, such as Silver-Sneakers (Flores et al, 2022), EnhanceFitness (Snyder et al, 2014), and Walk with Ease (Arthritis Foundation, 2002) may have also contributed to increasing physical activity levels over the past two decades. Throughout the observation period, males had a higher prevalence of meeting guidelines than females.…”
Section: Discussionmentioning
confidence: 99%
“…79 A retrospective cohort study in Washington state found an association between intermittent Silver Sneakers use and lower falls risk compared with nonusers (HR, 0.93; 95% CI, 0.90-0.97; absolute benefit not reported). 80 Free online fall exercise programs are available for those in rural areas or those without reliable transportation 81 although effectiveness data are lacking. Home safety evaluations by occupational therapy can be ordered for homebound older adults who are receiving skilled home care services.…”
Section: Practical Considerations and Application Of Evidencementioning
confidence: 99%